The Affectivity of Knee and Hip Muscle Strengthening Exercise to Improve Muscle Strength, Balance, Pain, and Functional Activity of People with Osteoarthritis (Medico Legal Update, 2020)
Introduction. Osteoarthritis is a common condition that affects elderly people, especially knee osteoarthritis.It can cause pain, muscle weakness, imbalance and low functional activity of elderly people. Kneeosteoarthritis not only affects muscles in the knee joint area but also those in the hip joint. To improvesymptoms of knee osteoarthritis, strengthening exercise is often conducted only on muscles in the kneejoint area, but not muscles in the hip area. This study aimed to compare the effect of strengthening exerciseconducted in knee joint muscles only with the strengthening exercise in both knee and hip muscles on pain,strength, balance and functional activity.Method. A pre- and posttest design was chosen as the design of this study. Two groups were formed inthis study. Group 1 received strengthening exercise on knee joint muscles only and Group 2 receivedstrengthening exercise on knee joint and hip joint muscles. This study was conducted in Prima Physio Clinicfor Group 1 and Tajuddin Chalid Hospital, Makassar for Group 2. On each group, there were 10 subjectswith osteoarthritis. The strengthening exercise was conducted for 3 times a week for 4 weeks. The outcomemeasure used was numeric pain rating scale (NPRS), manual muscle strength (MMT), Berg balance scale(BBS) and Western Ontario McMaster (WOMAC). Manual muscle strength was measured in all majormuscles of the joints: iliopsoas, gluteus, tensor fascia lata, quadriceps and hamstring.Results. The statistical analysis was conducted using Wilcoxon and Mann Whitney tests. In group 1 analysis,pain, balance, functional activity, and all major muscle strengths were found to be a statistically significantdifference between baseline and 4 weeks post-exercise. In group 2 analysis, pain, muscle strength, balance,and functional activity were found to be a statistically significant difference (p